Illustrating Ecologies - Bradley Cantrell (Oz, 2011)
In an attempt to understand the complex relationships occurring within ecological systems, methods of representation must explore modes that focus on illustration, simulation and dynamic modeling. Illustrating Ecologies, an advanced research seminar at the Louisiana State University Robert Reich School of Landscape Architecture, explores animating and modeling ephemeral ecological systems through analog and digital models.